THE IMPACT OF PERCEIVED VALUE ON CUSTOMER SATISFACTION AND REPURCHASE INTENTION OF BLACKBERRY USERS IN MANADO - Frendy, Jerdinan Septian (Universitas Sam Ratulangi, 2013)
People today are varying with different perception toward their purchasing behavior. They become eager in purchasing product to guarantee they satisfied after used the product. Blackberry smartphone in the last 4 years became very popular in society at global market nowadays. BlackBerry smartphone nowadays in Indonesia is turn into popular smartphone that already have by many people in every group of them. This research wants to study about customer perceived value on customer satisfaction and repurchase intention of BlackBerry users in Manado. The type of research used in this research is Structural Equation Modeling, or SEM is a quantitative study with secondary data collection techniques. This study collected 200 data sample of population of people who used BlackBerry smartphone in Manado. The conclusion of this study is perceived value has significantly effect toward customer satisfaction. Perceived value has positive effect to repurchase intention but did low significant effect. Customer satisfaction has positive and significant effect to repurchase intention. BlackBerry Ltd. company should be more consider about their strategic marketing and management on pricing by giving low cost (low price) to customer without decreasing the quality of product. Keywords: perceived value, customer satisfaction, repurchase intention